1991
DOI: 10.1002/jsfa.2740550308
|View full text |Cite
|
Sign up to set email alerts
|

Gross composition, amino acid, phytic acid and trace element contents of thirteen cowpea cultivars and their nutritional significance

Abstract: Thirteen cultivars of cowpea (Vigna unguiculata ( L ) Walp) were analysed for their proximate composition, amino acid, trace element and phytic acid contents. Crude protein values rangedfrom 206.8 to 2833 g k g -DM. The mean contents (g kg-') of other major nutrients were ether extract, 18.6; ash, 38.8; total dietary jibre, 121.8 and carbohydrates, 573.4. When compared with the provisional amino acid scoring pattern of FAO, all cultivars were low in methionine and high in lysine, isoleucine, leucine and pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Except for tryptophan and isoleucine, whose concentration in seeds obtained from the three locations appeared similar, seeds from Ago-Iwoye had higher and lower concentrations of threonine and leucine, respectively, when compared to Mokwa and Kano which recorded similar concentrations. In agreement with previous reports (Bressani 1985 ;Kochhar et al 1988 ;Farinu and Ingrao 1991), cowpea protein is deÐcient in sulphur amino acids cystine and methionine (FAO/WHO 1973), but has relatively high lysine, arginine and leucine contents. The relatively high lysine content makes cowpea an excellent improver of the protein quality of cereal (Bressani 1985).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Except for tryptophan and isoleucine, whose concentration in seeds obtained from the three locations appeared similar, seeds from Ago-Iwoye had higher and lower concentrations of threonine and leucine, respectively, when compared to Mokwa and Kano which recorded similar concentrations. In agreement with previous reports (Bressani 1985 ;Kochhar et al 1988 ;Farinu and Ingrao 1991), cowpea protein is deÐcient in sulphur amino acids cystine and methionine (FAO/WHO 1973), but has relatively high lysine, arginine and leucine contents. The relatively high lysine content makes cowpea an excellent improver of the protein quality of cereal (Bressani 1985).…”
Section: Resultssupporting
confidence: 90%
“…The threonine values showed the amino acid as the third limiting amino acid for most of the cultivars used in this study. Farinu and Ingrao (1991) obtained similar results. The analysis of variance for yield, protein, lipid and essential amino acid composition are presented in Table 3.…”
Section: Resultssupporting
confidence: 90%
“…phytate and tannin) in vegetables because of their adverse effects (Farinu and Ingrão, 1991;Câmara and Madruga, 2001). The values obtained for the anti-nutritional factors -phytate and tannin -of the flours analysed can be found in Table 3.…”
Section: Anti-nutritional Factorsmentioning
confidence: 99%
“…On the other hand, the most utilized sources of cereal fibre which are considered to be rich in phytate, such as barley (1000 mg/100g) and rice cereal (980 mg/100g), or rice grains (4900 -6900 g/100g) (Reddy et al, 1989), show significantly higher values than those found in the flours studied in this work. Ingestion of high levels of phytate has been associated with adverse anti-nutritional effects in humans, since these compounds are known to reduce bioavailability of proteins and minerals and inhibit the action of amylolytic and proteolytic enzymes (Serraino et al, 1985;Farinu and Ingrão, 1991;Chung et al, 1998;Câmara and Madruga, 2001). However, these's also a positive role for phytate in the human body, such as risk reduction of colon cancer, (Shamsuddin, 1992;Jenab and Thompson, 2002), and antioxidant action (Empson et al, 1991).…”
Section: Anti-nutritional Factorsmentioning
confidence: 99%
“…Thus, the genetic Information are available on the variability in yield and related characters (Eskine and Khan 1977), and recently on yield, protein, lipid and essential amino acids composition over environments (Oluwatosin 1997). Similarly, there were studies on the variability of fatty acids (Piergiovanni et al 1990) and trace elements (Farinu and Ingrao 1991) composition in some cowpea cultivars. However, despite the great nutritional and physiological importance of starch, fatty acids and mineral nutrients in cowpea seeds, very little is known about their variability over the di †erent agroecological zones where cowpeas are widely grown and consumed in Nigeria.…”
Section: Introductionmentioning
confidence: 99%